A global gircadian gepressor controls antiphasic expression of metabolic genes in neurospora - Sancar, Gencer; Sancar, Cigdem; Brügger, Britta; Ha, Nati; Sachsenheimer, Timo; Lohmann, Ingrid; Wieland, Felix T.; Höfer, Thomas; Diernfellner, Axel; Brunner, Michael (Molecular cell, 2011)
The white-collar complex (WCC), the core transcription factor of the circadian clock of Neurospora, activates morning-specific expression of the transcription repressor CSP1. Newly synthesized CSP1 exists in a transient complex with the corepressor RCM1/RCO1 and the ubiquitin ligase UBR1. CSP1 is rapidly hyperphosphorylated and degraded via UBR1 and its ubiquitin conjugase RAD6. Genes controlled by CSP1 are rhythmically expressed and peak in the evening (i.e., in antiphase to morning-specific genes directly controlled by WCC). Rhythmic expression of these second-tier genes depends crucially on phosphorylation and rapid turnover of CSP1, which ensures tight coupling of CSP1 abundance and function to the circadian activity of WCC. Negative feedback of CSP1 on its own transcription buffers the amplitude of CSP1-dependent oscillations against fluctuations of WCC activity. CSP1 predominantly regulates genes involved in metabolism. It controls ergosterol synthesis and fatty acid desaturases and thereby modulates the lipid composition of membranes.